(untitled) (Public Sector Economics - submission site, 2024)
The purpose of this study is to test whether the relationship between external debt and economic growth is symmetric or asymmetric in South Africa using annual time series data from 1985 to 2021. The study employed NARDL bounds and Breitung nonparametric cointegration estimation methods. Breitung, Bierens nonparametric, and ZA unit root test are used to check for the order of integration of the variables. The results from NARDL bounds and Breitung nonparametric cointegration test confirm a long run relationship between the variables. The results indicate that the responsiveness of GDP to positive shocks of external debt is less than that to negative shocks. An increase in external debt is associated with a decrease in GDP, while a decrease in external debt is associated with an increase in GDP. The study suggests that South African economy should keep its external debt sustainable so as not to harm economic growth.